2019
DOI: 10.5194/nhess-19-1685-2019
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis for satellite-index-based insurance to define damaged pasture thresholds

Abstract: Abstract. Vegetation indices based on satellite images, such as the normalized difference vegetation index (NDVI), have been used in countries like the USA, Canada and Spain for damaged pasture and forage insurance over the last few years. This type of agricultural insurance is called satellite-index-based insurance (SIBI). In SIBI, the occurrence of damage is defined as normal distributions. In this work a pasture area at the north of the Community of Madrid (Spain) has been delimited by means of Moderate Res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In fact, multiple authors [64,65] have reported a clear relationship between grasslands vegetation and water availability. In this line, the amount, variability, and timing of precipitation and temperature are determining factors of grassland production [6,66].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, multiple authors [64,65] have reported a clear relationship between grasslands vegetation and water availability. In this line, the amount, variability, and timing of precipitation and temperature are determining factors of grassland production [6,66].…”
Section: Discussionmentioning
confidence: 99%
“…The amount and timing of precipitation controls grasslands productivity, inducing fluctuations in soil water content throughout the seasons [5]. Temperature can regulate plant growth and reduce water availability in spring and fall in Mediterranean areas [6]. Therefore, it is essential to understand how drought affects grasslands, as these events are expected to increase with climatic change [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This special issue collects several papers that present an overview of risk management frameworks (Nastos et al, 2021) and provide several examples of their application. Particularly important is the role of the presented methods for the insurance sectors (Martín-Sotoca et al, 2019;Valverde-Arias et al, 2020): in a context of a changing climate, the use of insurance to protect the income of farmers will be crucial, especially in developing countries, which are particularly vulnerable to the changing climate and where the income from farming activities is the only source of income. Natural hazards, hydrology, and meteorology and climate sciences are often linked, and some of the papers included in the special issue confirm this close connection.…”
Section: Discussionmentioning
confidence: 99%
“…This product is a level-3 composite of the 500-m resolution, and the best pixel observation was chosen within eight days. The selection criteria for the best pixel observation were the aerosol content, view and solar zenith angle, cloud presence and clouds shadows [ 48 , 49 ].…”
Section: Methodsmentioning
confidence: 99%